Fuzzy agent-based model for learning behavior in formal education - Nur Syafikah, Sukri (2019)
The student group behavior emerges from interaction with fellow students and teachers, emotional and social influence, interaction with environment, teaching style and personal characteristic (e.g., self-efficacy). Since the student behavior is a complex system, the best solution for modelling this type of system of interacting agents is by using agent-based modelling. Agent-based modelling is good in handling the arising of system complexities, however in this system that involves with social relationship and human behavior, the subject uncertainty also include which are not accounted in this model. So, fuzzy logic is implement in this study since fuzzy logic can deals with vagueness and subject uncertainty. Integrating both agent-based model with fuzzy logic is a good idea in determining the learning behavior of student in education. In this study, the process of integrating fuzzy model with agent-based model is explained. Finally the development of fuzzy agent-based model of student group is present to allow the prediction of learning behavior of student. The contribution that we made of this paper is the process of integrating fuzzy logic with agent-based model in student group to determine the learning style is well-explained.